2013
DOI: 10.1104/pp.113.227595
|View full text |Cite
|
Sign up to set email alerts
|

A Wheat Allene Oxide Cyclase Gene Enhances Salinity Tolerance via Jasmonate Signaling    

Abstract: One of the two branches of the a-linolenic acid metabolism pathway is catalyzed by 12-oxo-phytodienoic acid reductase I, and the other is involved in jasmonic acid (JA) synthesis. The former is known to be active in the response to salinity tolerance in wheat (Triticum aestivum), but the participation of the latter in this response has not been established as yet. Here, the salinity-responsive bread wheat gene TaAOC1, which encodes an allene oxide cyclase involved in the a-linolenic acid metabolism pathway, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(144 citation statements)
references
References 52 publications
4
140
0
Order By: Relevance
“…SAHA treatment enhanced MeAOC4 expression to 32.8-fold compared with untreated plants (Figure 7A). Previous studies have revealed that overexpression of AOCs can confer salinity stress tolerance to several crops (Yamada et al, 2002; Pi et al, 2009; Zhao et al, 2014). According to the current cassava genome database, AOCs constitute a small gene family ( MeAOC3-1 : RknMes02_049533: cassava4.1_014582m; MeAOC3-2 : RknMes02_054684: cassava4.1_026961m; and MeAOC4 : RknMes02_051874: cassava4.1_022180m) in cassava (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SAHA treatment enhanced MeAOC4 expression to 32.8-fold compared with untreated plants (Figure 7A). Previous studies have revealed that overexpression of AOCs can confer salinity stress tolerance to several crops (Yamada et al, 2002; Pi et al, 2009; Zhao et al, 2014). According to the current cassava genome database, AOCs constitute a small gene family ( MeAOC3-1 : RknMes02_049533: cassava4.1_014582m; MeAOC3-2 : RknMes02_054684: cassava4.1_026961m; and MeAOC4 : RknMes02_051874: cassava4.1_022180m) in cassava (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…AOC regulates a crucial step in JA biosynthesis, and the JA derivative, MeJA, alleviates salt stress in soybean (Yoon et al, 2009). The constitutive expression of AOCs can confer salinity tolerance to plants such as tobacco cell lines (Yamada et al, 2002) and wheat (Zhao et al, 2014), and references for the involvement of JA in environmental stresses can be found in Riemann et al (2015). In light of these findings, it is highly possible that overexpression of MeAOC4 contributes to increased tolerance to salt stress under SAHA treatment in cassava.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic expression of several genes involved in JA biosynthesis and signaling pathway showed enhanced salt tolerance [6668]. The pathway component EIN3 performed as a positive regulator on salt stress tolerance, further studies found the downstream ERF1 selectively actives salt tolerance genes by binding to the DRE-box of these genes promoter [69, 70].…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of TaAOC1 enhanced salinity tolerance in wheat via a JA pathway-dependent manner. 13 Furthermore, wheat genes belonging to the WRKY and MYB transcription factor family have been found to be differentially expressed in wheat under conditions of biotic and abiotic stress, such as Fusarium graminearum infection, extreme temperatures (3 C and 40 C), high salinity stress (10% NaCl), osmotic stress and treatment with SA. 14,15 However, up-to-date information on plant gene expression during JA signaling in wheat is fragmented and is only presented for either shoots or roots.…”
Section: Introductionmentioning
confidence: 99%